SPECIFICITIES OF CORPORATE GOVERNANCE IN SMALL BUSINESS ENTERPRISES OF UZBEKISTAN - Zufar Ashurov (Journal of Management Small and Medium Enterprises (SMEs), 2015)
It is commonly known that the corporate governance is a way of management which is intrinsic tothe large corporate structures. Today, in Uzbekistan such corporate structures mainly function inthe form of joint-stock companies, limited liability companies, additional liability companies,general partnerships, limited partnership where there introduced a governance practice on the basisof corporate governance principles. This paper theoretically investigates the concept of corporategovernance in SMEs, and studies the specificities of corporate governance practice in small businessenterprises of Uzbekistan. At the end of this paper, the author makes conclusion and gives somerecommendations on further improvement of activity of small business enterprises to function as a“corporate” type business entity. Keywords: Corporate Governance, SME, Small Business Enterprises, Limited LiabilityCompany, Additional Liability Company, General Partnership, Limited Partnership, FamilyEnterprise